A crônica e a prática escolar de leitura no ensino médio - Lima, Sandra Araújo (2012)
This work deals with the chronicle, a hybrid textual genre whose main communicative purpose is to comment and provoke reflections about facts, people, situations and themes of daily life. The research has the objective of verifying to what extent the cited genre has contributed for meaningful reading practices in Portuguese Language lessons in High School specifically in two public state schools and in two private schools in the municipality of Arapiraca, in the interior of Alagoas, a state in the Northeast of Brazil. The research is characterized as interpretative, qualitative and ethnographic, although also takes into consideration some quantitative data which were qualitatively analyzed. In order to collect data, the author utilized questionnaires and interviews with students and eachers. The theoretical basis of the work is found in ideas and theories of authors such as Kleiman (2009), Solé (2008) and Marcuschi (2008), Silveira (2005) among others. In addition, the author presented studies on the chronicle as a textual genre, its evolution, types and discursive features. The results of the research carried out demonstrated that the chronicle is a genre appreciated by the informant students and teachers; however, it is necessary to increase reading practices with the chronicle in High School in the institutions where the research was carried out, especially in private schools.